Molecular pathogenesis of endometrial cancers in patients with Lynch syndrome. Issue 16 (12th June 2013) - Huang, Marilyn; Djordjevic, Bojana; Yates, Melinda S.; Urbauer, Diana; Sun, Charlotte; Burzawa, Jennifer; Daniels, Molly; Westin, Shannon N.; Broaddus, Russell; Lu, Karen
<x xml:space="preserve">Abstract</x> BACKGROUND The authors hypothesized that Lynch syndrome (LS)‐associated endometrial cancer (EC) develops from morphologically normal endometrium that accumulates enough molecular changes to progress through a continuum of hyperplasia to carcinoma, similar to sporadic EC. The primary objective of the current study was to determine whether LS‐associated EC involves progression through a preinvasive lesion. The secondary objective was to identify molecular changes that contribute to endometrial carcinogenesis in patients with LS. METHODS Women with a confirmed mismatch repair gene mutation for LS who were undergoing a prophylactic or therapeutic hysterectomy were eligible. Cases and controls were matched for EC and hyperplasia based preferentially on age and histology. Mutation status of phosphatidylinositol 3‐kinase (PIK3CA); KRAS; AKT; LKB1; catenin (cadherin‐associated protein), beta 1, 88kDa (CTNNB1); and phosphatase and tensin homolog (PTEN) protein loss was assessed. RESULTS Concurrent complex atypical hyperplasia (CAH) was found in EC in 11 cases of LS (39.3%) and 21 sporadic cases (46.6%). Loss of PTEN expression was common in both sporadic (69%) and LS‐associated EC (86.2%). There was no significant difference noted with regard to the frequency of KRAS mutations in cases of sporadic EC (10.3%) compared with LS‐associated EC (3.4%). AKT and LKB1 mutations were rarely observed. Mutations in PIK3CA and CTNNB1 occurred more frequently in cases of sporadic EC compared with LS‐associated EC. CONCLUSIONS Hyperplasia, particularly CAH, is part of the preinvasive spectrum of disease in LS‐associated EC, as indicated by the presence of complex hyperplasia and CAH in cases of LS. Although loss of PTEN is common in both LS and sporadic EC cases, there was a lack of additional mutations in LS‐associated EC cases. This suggests that in the context of the mismatch repair defects in LS, fewer additional molecular changes are required to progress from preinvasive lesions to cancer. Cancer 2013;119:3027—3033. © 2013 American Cancer Society.